Isolation and Characterization of the First Xylanolytic Hyperthermophilic Euryarchaeon Thermococcus sp. Strain 2319x1 and Its Unusual Multidomain Glycosidase - Gavrilov, Sergey N.; Stracke, Christina; Jensen, Kenneth; Menzel, Peter; Kallnik, Verena; Slesarev, Alexei; Sokolova, Tatyana; Zayulina, Kseniya; Bräsen, Christopher; Bonch-Osmolovskaya, Elizaveta A.; Peng, Xu; Kublanov, Ilya V.; et al. (Frontiers in Microbiology, 2016)
Enzymes from (hyper)thermophiles “Thermozymes” offer a great potential for biotechnological applications. Thermophilic adaptation does not only provide stability towards high temperature but is also often accompanied by a higher resistance to other harsh physicochemical conditions, which are also frequently employed in industrial processes, such as the presence of e.g. denaturing agents as well as low or high pH of the medium. In order to find new thermostable, xylan degrading hydrolases with potential for biotechnological application we used an in situ enrichment strategy incubating Hungate tubes with xylan as the energy substrate in a hot vent located in the tidal zone of Kunashir Island (Kuril archipelago). Using this approach a hyperthermophilic euryarchaeon, designated Thermococcus sp. strain 2319x1, growing on xylan as sole energy and carbon source was isolated. The organism grows optimally at 85°C and pH 7.0 on a variety of natural polysaccharides including xylan, carboxymethyl cellulose (CMC), amorphous cellulose (AMC), xyloglucan, and chitin. The protein fraction extracted from the cells surface with Twin 80 exhibited endoxylanase, endoglucanase and xyloglucanase activities. The genome of Thermococcus sp. strain 2319x1 was sequenced and assembled into one circular chromosome. Within the newly sequenced genome, a gene, encoding a novel type of glycosidase (143 kDa) with a unique five-domain structure, was identified. It consists of three glycoside hydrolase (GH) domains and two carbohydrate-binding modules (CBM) with the domain order GH5-12-12-CBM2-2 (N- to C-terminal direction). The full length protein, as well as truncated versions, were heterologously expressed in Escherichia coli and their activity was analyzed. The full length multidomain glycosidase (MDG) was able to hydrolyze various polysaccharides, with the highest activity for barley β-glucan (β-1,3/1,4-glucoside), followed by that for carboxymethyl cellulose (β-1,4-glucoside), cellooligosaccharides and galactomannan. The results reported here indicate that the modular MDG structure with multiple glycosidase and carbohydrate-binding domains not only extends the substrate spectrum, but also seems to allow the degradation of partially soluble and insoluble polymers in a processive manner. This report highlights the great potential in a multi-pronged approach consisting of a combined in situ enrichment, (comparative) genomics, and biochemistry strategy for the screening for novel enzymes of biotechnological relevance.